A SECURE AND EFFICIENT AUTHENTICATION WITH KEY AGREEMENT SCHEME BASED ON ELLIPTIC CURVE CRYPTOSYSTEM - Qu, Juan; Feng, Yuming; Huang, Yi (Italian Journal of Pure and Applied Mathematics, 2015)
Recently, Li et al. [20] proposed an improved authentication with key agreement scheme on elliptic curve cryptosystem for global mobility networks to remedy the weaknesses of Rhee et al.’s scheme. Li et al.’s scheme not only achieves mutual authentication, but also provides the procedure for key agreement and updates of secrets for users and servers. However, we find that Li et al.’s scheme is still insecure and vulnerable to insider attack, impersonation attack and unverifiable password change. In order to eliminate these pitfalls, we propose a new authenticated with key agreement scheme based on elliptic curve cryptosystem. The analysis shows that the proposed scheme is more secure and more suitable for global mobility networks.